Varilaku: Pacific Arts from the Solomon Islands - Howarth, Crispin with Waite, Deborah (Australia National Gallery of Australia, 2011)
Through the finest traditional Solomon Islands art in Australia's museums and galleries, Varilaku explores kastom beliefs in ancestral ghosts, the world of spirit beings, ocean-bound raiding expeditions, and the Indigenous aesthetics of the self--the use of adornments to express identity and status from the mid-19th century to the mid-20th century.
Includes Colored Illustrations and Index.
Keywords: Art, Solomon Islands -- Exhibitions